2005
DOI: 10.1158/1055-9965.epi-04-0583
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, Recreational Physical Activity, and Risk of Pancreatic Cancer In a Large U.S. Cohort

Abstract: Background: Obesity and physical activity, in part through their effects on insulin sensitivity, may be modifiable risk factors for pancreatic cancer. Methods: The authors analyzed data from the American Cancer Society Cancer Prevention Study II Nutrition Cohort to examine the association between measures of adiposity, recreational physical activity, and pancreatic cancer risk. Information on current weight and weight at age 18, location of weight gain, and recreational physical activity were obtained at basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
209
3
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 285 publications
(233 citation statements)
references
References 38 publications
15
209
3
6
Order By: Relevance
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women.…”
Section: Discussionmentioning
confidence: 95%
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More than half the studies in this area show an inverse relationship between physical activity and PC, [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] other studies show no association [31][32][33][34][35][36][37][38][39][40][41][42] and four studies even found exercise increased PC risk. [43][44][45][46] Perhaps this uncertainty in the literature can be attributed to the epidemiological nature of the research designs utilized in these studies, which relied upon survey or patient self-reporting to elicit physical activity and/or exercise exposure.…”
Section: Exercise and Prostate Cancer Preventionmentioning
confidence: 99%